Are TNF inhibitors still the agent of choice for RA? - Taylor, PC (Springer Nature, 2023)
Since entering the clinic 25 years ago, biologic TNF inhibitors have transformed the outlook for people with rheumatoid arthritis and set the standard for all other targeted therapies. Despite changes to the therapeutic landscape, TNF inhibitors look set to remain an important treatment option for the foreseeable future.